How disasters affect local labor markets: the effects of hurricanes in Florida - Ariel R. Belasen; Solomon W. Polachek (Institute for the Study of Labor (IZA), 2007)
Exogenous shocks often impact a local labor market more than at the national level. This study improves upon the standard Difference in Difference (DD) approach by examining exogenous shocks using a Generalized Difference in Difference (GDD) econometric approach that identifies the effects of shocks resulting from hurricanes. Based on the Quarterly Census of Employment and Wages (QCEW) data on earnings and employment, the earnings of an average worker in Florida will increase as much as four percent within the first quarter of being hit directly by a hurricane, whereas the effects of a hurricane occurring in a neighboring county move earnings per worker in the opposite direction by roughly the same percentage. As time goes by, workers in both sets of counties will experience faster growth in their earnings than workers in completely unaffected counties; however, this is coupled with a slower growth rate in employment. Powerful hurricanes have greater effects than their weaker counterparts. Additionally, the shifts in earnings and employment can be traced back, in part, to geographic features of the counties, namely that the coastal and Panhandle counties exhibit greater effects than landlocked counties. Although focus is on hurricanes in Florida, this GDD technique is applicable to a wider range of exogenous shocks.
Keywords: 330; Sturm; Schock; Regionaler Arbeitsmarkt; Regionale Lohnstruktur; Statistischer Test; Florida; USA; Sturm; Regionaler Arbeitsmarkt; USA; Arbeitsmarkt; Beschäftigung; Lohn; Florida